Digital bookkeeping solutions for Micro-, Small & Medium Enterprises (MSMEs) / Fauziah Mohamad Yunus and Dr. Chaleeda Som Sak - Mohamad Yunus, Fauziah; Som Sak, Chaleeda (Universiti Teknologi MARA, Kedah, 2023)
The rise of commerce, specifically during the commercial revolution back from the years 1250 and 1350, led to the development of the debit and credit system in accounting, hence giving birth to the concept of bookkeeping (Gröblacher & Mizdrakovic, 2019). Since then, bookkeeping has been playing an important role in dealing with day-to-day financial records, from invoices to payments. Although bookkeeping has been around for a very long time, some Micro-, Small & Medium Enterprises (MSMEs) in Malaysia are still old-fashioned, without have a good way to keep track of their income and expenses; in other words, they do not know how much their business is making or spending. For some MSMEs, handwritten notes are still used in sales transactions in the traditional style. In addition, the notes used are in duplicate, the first note for buyers and the second note for store data (Ledgerwood, 1999). This occurs daily, and the sales report is solely based on the sales note. In this regard, the presentation of records and the preparation of reports always take more time. Hence, the information conveyed is not effective and adequate. For instance, if the sales notes are lost or damaged, there is no backup copy, and the transactions could not be traced back. This will make it harder for business owners to gather information for preparing a financial statement in the future. For many other MSMEs, they utilize Microsoft Excel as their computerized accounting system. However, this is considered inadequate due to its manual nature, requiring accounting procedures to be typed in, resulting in a time-consuming process (Ibrahim et al., 2020). Furthermore, using Excel for reporting purposes provides estimated monthly profits instead of accurate financial performance information. Although there are many bookkeeping apps available, many MSMEs have yet to take advantage of them. Not only does it possess the risks of privacy, security, and information loss, but many also find the bookkeeping apps need to be purchased and challenging to use, preferring traditional bookkeeping methods (Kumari & Kumar, 2023). Generally, MSMEs in Malaysia are still behind in terms of technology. Figure 1 below shows the diffusion rate, median OECD, based on Malaysia’s average percentages of enterprises using the technology over 2015 – 2018. The figure illustrates that SME gaps in the adoption of technology are still large in many areas. In fact, they are failing to keep up with the borderless digital economy and the Industrial Revolution 4.0 due to their inadequate learning and adaptation to these rapidly evolving changes (Small Medium Enterprise Development Bank, 2020). This causes the business decisions made are based on an ad hoc basis due to the lack of information systems that can provide reliable information (Hosen et al., 2020).